Quantum Topological Neural Operators and Digital Twin Intelligence for Multiscale Climate, Energy, Hydrological, Urban, Industrial and Health Systems - Murali Krishna Pasupuleti (International Journal of Academic and Industrial Research Innovations(IJAIRI), 2026)
Abstract: Complex climate, energy, hydrological, urban, industrial and health systems are increasingly monitored through heterogeneous sensor, simulation and observational infrastructures, yet their digital twins remain fragmented by domain-specific models, incompatible scales and weak representations of nonlinear topology. This paper develops a unified model-based framework termed Quantum Topological Neural Operator Digital Twin Intelligence (QTNODT). The framework combines persistent and graph-topological representations, quantum or quantum-inspired feature encodings, neural operators for learning solution mappings between function spaces, digital-twin data assimilation, uncertainty quantification and risk-aware optimisation. The study synthesises the supplied literature on neural operators, quantum machine intelligence, topological learning, smart-grid stability, water twins, urban resilience, predictive-maintenance twins, climate-risk modelling and multimodal health intelligence. A coupled mathematical formulation is proposed in which sector states evolve through dynamic operators and are linked by cross-sector interaction matrices, while topological signatures act as scale-robust structural constraints. A normalized 0-10 numerical demonstration yields a weighted domain score of 8.141 and a risk-adjusted QTNODT score of 7.813 under an illustrative uncertainty penalty, indicating how readiness, twin fidelity, topological stability, computational capacity and governance can be combined without presenting simulated values as empirical evidence. The framework contributes a common analytical language for cross-domain forecasting, resilience assessment and intervention design. Its principal value is methodological: it specifies testable interfaces among data, topology, operators, twins and decisions, while making clear that empirical validation requires real-world sector datasets, benchmark comparisons and prospective evaluation. Keywords: quantum topological intelligence; neural operators; digital twins; persistent homology; graph topology; climate risk; smart grids; hydrological intelligence; urban resilience; Industry 5.0; predictive maintenance; precision health; uncertainty quantification; multiscale systems; scientific machine learning